The Prognostic Value of Nanog Overexpression in Lung Cancer: A Meta-Analysis. (3rd December 2018) - Cheng, Wei; Wang, Hongzhi; Yuan, Juanjuan; Cheng, Ziwei; Xing, Dongwei; Zhang, Minguang
Abstract : Background . Recent several studies have showed that the nanog overexpression leads to poor prognosis in some kinds of cancer including hepatocellular carcinoma and gastrointestinal luminal cancer. However, the correlations between prognosis and clinic-pathological features and nanog overexpression in lung cancer are still not well-known. Thus, we performed a meta-analysis to evaluate the role of nanog in lung cancer. Methods . An electronic retrieval for related studies was conducted in PubMed, Cochrane Library, Web of Science, EMBASE databases, Chinese CNKI, and the Chinese Wan Fang database up to May 2018. The relationships between nanog overexpression and overall survival (OS) and disease-free survival (DFS) as well as clinic-pathological features in lung cancer were investigated. Pooled hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated by STATA12. Results. 11 studies containing 1422 patients were identified in our meta-analysis. The overexpression of nanog showed decreased OS (HR = 1.83, 95% CI = 1.49-2.25, P ≤ 0.001) and DFS (HR = 1.86, 95% CI = 1.2-2.9, P = 0.006). Moreover, overexpression of nanog was significantly related to differentiation (OR = 4.17, 95% CI = 2.17-6.43, P ≤ 0.001), lymph node metastasis (OR = 1.76, 95% CI = 1.06-2.91, P = 0.028) and tumor size (OR = 1.93, 95% CI = 1.17-3.20, P = 0.010), and no correlation with T stage, TNM, stage, and gender. Conclusions. Our results suggested that nanog overexpression, a hazard factor of differentiation, lymph node metastasis, and tumor size, may predicate decreased OS and DFS for lung cancer.